58.9k views
5 votes
The line $y = 3$ intersects the graph of $y = 4x^2 + x - 1$ at the points $A$ and $B$. The distance between $A$ and $B$ can be written as $\frac{\sqrt{m}}{n}$, where $m$ and $n$ are positive integers that do not share any factors other than one. Find the value of $m - n$.

2 Answers

0 votes

Answer:

61

Explanation:

Let's find the points
A and
B.

We know that the
y-coordinates of both are
3.

So let's first solve:


3=4x^2+x-1

Subtract 3 on both sides:


0=4x^2+x-1-3

Simplify:


0=4x^2+x-4

I'm going to use the quadratic formula,
x=(-b\pm √(b^2-4ac))/(2a), to solve.

We must first compare to the quadratic equation,
ax^2+bx+c=0.


a=4


b=1


c=-4


(-1 \pm √(1^2-4(4)(-4)))/(2(4))


(-1 \pm √(1+64))/(8)


(-1 \pm √(65))/(8)

Since the distance between the points
A and
B is horizontal. We know this because they share the same
y-coordinate.This means we just need to find the positive difference between the
x-values we found for the points of
A and
B.

So that is, the distance between
A and
B is:


(-1+√(65))/(8)-(-1-√(65))/(8)


(-1+√(65)+1+√(65))/(8)


(2√(65))/(8)


(√(65))/(4)

If we compare this to
(√(m))/(n), we should see that:


m=65 \text{ and } n=4.

So
m-n=65-4=61.

User Denis Ali
by
6.5k points
2 votes

Answer:

m - n = 61

Explanation:


y=4x^2+x-1\\\\y=3\\\\\text{Find the points A and B}.\\\\4x^2+x-1=3\qquad\text{subtract 3 from both sides}\\\\4x^2+x-1-3=3-3\\\\4x^2+x-4=0


\text{Use the quadratic formula:}\\\\a=4,\ b=1,\ c=-4\\\\b^2-4ac=1^2-4(4)(-4)=1+64=65\\\\x=(-b\pm√(b^2-4ac))/(2a)\to x=(-1\pm√(65))/(2(4))=(-1\pm√(65))/(8)


\text{Therefore}\\\\A\left((-1-√(65))/(8),\ 3\right),\ B\left((-1+√(65))/(8),\ 3\right)\\\\\text{The formula of a distance between two points:}\\\\d=√((x_2-x_1)^2+(y_2-y_1)^2)\\\\\text{Substitute:}\\\\d=\sqrt{\left((-1+√(65))/(8)-(-1-√(65))/(8)\right)^2+(3-3)^2}\\\\d=\sqrt{\left((-1+√(65)-(-1)-(-√(65)))/(8)\right)^2+0^2}\\\\d=\sqrt{\left((-1+√(65)+1+√(65))/(8)\right)^2}\\\\d=\sqrt{\left((2√(65))/(8)\right)^2}


d=\sqrt{\left((√(65))/(4)\right)^2}\Rightarrow d=(√(65))/(4)\Rightarrow(√(65))/(4)=(√(m))/(n)\\\\\text{Therefore}\ m=65\ \text{and}\ n=4\\\\m-n=65-4=61

User John Korsnes
by
6.6k points